Pharmacokinetic drug evaluation of ribociclib for the treatment of metastatic, hormone-positive breast cancer. (4th May 2017) - Curigliano, Giuseppe; Criscitiello, Carmen; Esposito, Angela; Intra, Mattia; Minucci, Saverio
ABSTRACT: Introduction : Cyclin D-cyclin-dependent kinase (CDK) 4/6-inhibitor of CDK4/6-retinoblastoma (Rb) pathway hyperactivation is associated with hormone receptor-positive (HR+) breast cancer (BC). Ribociclib is an orally bioavailable, highly selective small molecule inhibitor of CDK4/6 that induces G1 arrest at sub-micromolar concentrations in a variety of pRb-positive cancer cells in vitro . Ribociclib is a new standard of care for metastatic HR+/HER2 negative metastatic breast cancer. Area covered : In this article, we review the preclinical and clinical development of ribociclib as well as discussing the role for novel applications of these agents outside the arena of HR-positive, HER2-negative advanced breast cancer. Expert opinion : Results of pivotal phase II and III trials investigating ribociclib in patients with advanced-stage (HR)-positive breast cancer have demonstrated a substantial improvement in progression-free survival, with a safe toxicity profile. Mechanisms of acquired resistance to CDK4/6 inhibitors are beginning to emerge and might enable rational post-CDK4/6 inhibitor therapeutic strategies to be identified. Extending the use of CDK4/6 inhibitors beyond ER-positive breast cancer is challenging, and will likely require biomarkers that are predictive of a response. The use of combination therapies to optimize CDK4/6 targeting is under development.